Ulcerozni kolitis - Breznik, Nika (Placebo, 2022)
Chronic inflammatory bowel disease is a group of inflammatory bowel diseases, including Crohn's disease, ulcerative colitis, and intermediate colitis. The most frequent form of inflammatory bowel disease is ulcerative colitis. Its incidence is higher in the developed world and is still growing. Ulcerative colitis is a gastrointestinal disease of unknown etiology, usually lasting a lifetime. It is characterized by a chronic course with frequent flares and intermediate periods of variable length of remission. Symptoms of ulcerative colitis are diverse. The most common are abdominal pain and blood in the stool. Some patients may experience extra-intestinal manifestations of the disease. Diagnosis of ulcerative colitis begins with an analysis of the patient's history and a clinical examination and is confirmed via the laboratory, radiological, endoscopic, and histological examinations. The purpose of treatment is to achieve remission and prevent disease onset. Healing is only possible with a complete colectomy
Keywords: inflammatory bowel disease; Kronična vnetna črevesna bolezen; ulcerative colitis; Ulcerozni kolitis